Effect of Investment Fraud on Individuals’ Risk Preference and Investment Portfolio - Yudhianto, Antonius; Atmaji, Atmaji (JDM (Jurnal Dinamika Manajemen), 2023)
This study aimed to determine the effect of investment fraud on individual risk preference and to determine the effect of investment fraud an individual investment portfolios. This is a descriptive study that employed a quantitative approach. The research population was the victim of investment fraud in the Solo Raya area. The sample was in the Solo Raya area which included 5 districts and 1 city. The research sample was taken using a non-probability sampling technique by applying a purposive sampling technique which resulted in 100 respondents. The results showed that Illegal Investment Fraud has a positive and significant effect on the Individual Risk Preference of investment fraud victims in the Solo Raya area. Illegal investment fraud has a negative and significant effect on the individual investment portfolio of investment fraud victims in the Solo Raya area. In other words, if illegal investment fraud increases, the investment portfolio of individuals who are victims of investment fraud in the Solo Raya area will decrease.